Enhanced anodic electrochemiluminescence of CdTe quantum dots based on electrocatalytic oxidation of a co-reactant by dendrimer-encapsulated Pt nanoparticles and its application for sandwiched immunoassays. Issue 20 (21st September 2017) - Ren, Lu-Lu; Dong, Hao; Han, Ting-Ting; Chen, Yun; Ding, Shou-Nian
Abstract : A first immunosensor using Fe3 O4 @SiO2 -Pt DENs for carrier separation and signal amplification in the CdTe QD-TPrA anodic ECL system. Abstract : Herein, we synthesized Pt dendrimer-encapsulated nanoparticles (Pt DENs) using amine-terminated sixth-generation polyamidoamine dendrimers. The enhanced and stable anodic electrochemiluminescence (ECL) of 3-mercaptopropionic acid-capped CdTe quantum dots (QDs) in a tripropylamine solution was achieved owing to Pt DENs. The reason may be that Pt DENs exhibit high catalytic electrochemical oxidation in the presence of tripropylamine and excellent conductive property. Inspired by this, Pt DENs were conjugated with Fe3 O4 @SiO2 nanoparticles and served as nano-carriers. The capture antibodies were immobilized on the Fe3 O4 @SiO2 -Pt DEN nanocomposites, which possess many attractive advantages such as the ease of bioconjugation, large specific surface area, and convenience of magnetic separation. Fluorescence microscopy images and UV-vis spectra were used to verify the immobilization of capture antibodies on the nanocomposites. The CdTe QDs were applied as signal labels for conjugation of nanocomposites with detection antibodies, which were characterized by agarose gel electrophoresis. Electrochemical impedance spectroscopy and cyclic voltammetry demonstrated the successful preparation of an ECL immunosensor. Under the optimal conditions, the proposed immunosensor provided a wide linear range from 0.005 ng mL −1 to 150 ng mL −1 with a detection limit of 0.2 pg mL −1 (S/N = 3) for the detection of carcinoembryonic antigen. Moreover, the immunosensor showed good performance for the detection of carcinoembryonic antigen in serum samples as well as great potential in clinical bioassay.